Analysis of Reticulocyte Hemoglobin Equivalent Levels in Patients with Chronic Kidney Disease Stage IV and V - Agri Febria Sari; Rikarni Rikarni; Deswita Sari (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Reticulocyte hemoglobin equivalent (RET-He) represents hemoglobin content in reticulocyte. Reticulocyte hemoglobin equivalent test can be used to asses iron status of chronic kidney disease (CKD). Iron deficiency happens in 40% CKD and could lead to anemia manifestation. Level of RET-He gives real-time assesment of iron availability for hemoglobin production and the level will getting lower when iron storage for erythropoiesis decreasing. Reticulocyte hemoglobin equivalent is more stabil than feritin and transferin saturation in assessing iron status. Aim of this study is to determine RET-He level in patients with CKD stage IV and V. This study is  a cross sectional descripstive study. Subjects were 96 CKD stage IV and V patients that met inclusion and exclusion criterias. Subjects conducted blood tests at Central Laboratory Installation Dr. M. Djamil Hospital Padang from July to September 2020. Examination of RET-He level was analyzed by Sysmex XN-1000 flowcytometry fluorescense method. Data was presented in frequency distribution table. The RET-He level below cutoff (<29,2 pg) indicates the need for iron suplementation therapy for CKD stage IV and V patients. Samples with RET-He level below cutoff were 48 (50%) and 48 (50%) were above cutoff.